Efficiency of medical rehabilitation program in early aged children with cystic fibrosis - V. S. Matveev; S. V. Matveev; A. A. Potapchuk; Iu. K. Uspenskaia (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2020)
Introduction. The problem is actual due to the increasing of cystic fibrosis children quantity: according to neonatal screening, there were 124 children with cystic fibrosis in 2018 (72.9 % from all identified cases for the reporting year). Medical rehabilitation is the main method of the pathogenetic therapy and prevention of cystic fibrosis exacerbation. The new strategy of medical procuring for patients with orphan diseases, which is necessary to develop expert methods for diagnostics of rehabilitation potency and objectify individual rehabilitation programs, gives particular relevance to the problem.The objective was the development of new rehabilitation programs for early aged children with cystic fibrosis, the search of efficiency assessment criteria.Methods and materials. Physical and motor growth, clinical and functional parameters were estimated in 79 early aged children of main and control groups.Results. It was proved that the weight index (absolute and relative), quantity of children with harmonic growth increased due to physical methods of rehabilitation while the quantity of children with acutely disharmonic growth reduced in main group. After applying the developed rehabilitation program, the formed motor skills amounted 83 — 92 % from age norm in the main group of children and 60 — 85 % in the control group. Normotonic reaction to physical activity after the physical rehabilitation program was registered in 73.2 % of the main group and 47.8 % of the control group. In dynamics, the rehabilitation efficiency coefficient amounted (1.68±0.10) in the control group of children and (1.97±0.14) (p<0.05) in the main group that could be corresponded as «improvement». That means the quality of clinical and laboratory shifts, dynamism of physical growth and development rate of motor skills is significantly higher in the main group of children.Conclusion. The possibility of physical rehabilitation use in different rehabilitation programs of early aged children with cystic fibrosis was justified. The rehabilitation efficiency coefficient, the rehabilitation potential were offered, the effectiveness of chosen rehabilitation programs was proved.